Isavuconazole treatment for rare fungal diseases and for invasive aspergillosis in patients with renal impairment: Challenges and lessons of the VITAL trial. Issue 7 (19th April 2018) - Perfect, John R.; Cornely, Oliver A.; Heep, Markus; Ostrosky‐Zeichner, Luis; Mullane, Kathleen M.; Maher, Rochelle; Croos‐Dabrera, Rodney; Lademacher, Christopher; Engelhardt, Marc; Chen, Caroline; Marty, Francisco M.
Summary: Invasive fungal disease (IFD) confers a substantial risk for morbidity and mortality to immunocompromised patients. Invasive aspergillosis (IA) is the most common IFD caused by moulds but the prevalence of other rare mould diseases, such as mucormycosis, hyalohyphomycosis and phaeohyphomycosis, may be increasing. Treatments are available for IA, but evidence to support efficacy and safety of antifungal agents for rare IFDs, or for IFDs in special patient populations, is limited or lacking. The VITAL trial was conducted to assess the efficacy and safety of isavuconazole for the treatment of patients with IA and renal impairment, or with IFDs caused by rare moulds, yeasts or dimorphic fungi. These patients stand to benefit most from a new treatment option but are unlikely to be included in a randomised, controlled trial. In this article, we review the challenges faced in the design and conduct of the VITAL trial. We also review the findings of VITAL, which included evidence of the efficacy and safety of isavuconazole. Finally, we consider the importance of trials such as VITAL to inform therapeutic decision making for clinicians faced with the challenge of treating patients with rare IFDs and as one paradigm of how to determine efficacy and safety of new drugs for rare and resistant infections without a suitable comparator.